2020
DOI: 10.20961/basastra.v8i2.43377
|View full text |Cite
|
Sign up to set email alerts
|

Muatan Pendidikan Karakter Dalam Cerita Pendek Di Buku Pelajaran Bahasa Indonesia Sma

Abstract: This study aims to (1) Describe short stories published in Indonesian textbooks for high school. (2) Describe the content of character education in short stories in Indonesian textbooks for high school. This research is a qualitative descriptive study. Data in this study are words, sentences and paragraphs in short stories in Indonesian textbooks for high school. Data sources in this study are Indonesian language textbooks for high schools which are still used in high school, both based on the 2006 curriculum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
0
5
0
2
Order By: Relevance
“…This finding is in line with the results of research by Sufanti, Purwanti and Cahyati which revealed that the attitude of tolerance is found in the characters in the short story entitled Telur Ayam Sebelum Fajar (Telur Ayam Before Dawn), that is, it contains characters who value differences of opinion. [15].…”
Section: Morals To Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in line with the results of research by Sufanti, Purwanti and Cahyati which revealed that the attitude of tolerance is found in the characters in the short story entitled Telur Ayam Sebelum Fajar (Telur Ayam Before Dawn), that is, it contains characters who value differences of opinion. [15].…”
Section: Morals To Humansmentioning
confidence: 99%
“…Research related to the nature of tolerance in the moral element towards humans was carried out by Sufanti, Purwanti and Cahyati who revealed that the attitude of tolerance is found in the character of the short story entitled Telur Ayam Sebelum Fajar (Chicken Eggs Before Dawn), yakThis is a character of respecting differences of opinion. The attitude of tolerance possessed by the characters in the story is illustrated when the characters allow people to disagree with them and are allowed to debate with them [15].…”
Section: Introductionmentioning
confidence: 99%
“…We live inevitably in need of the existence of others to interact with each other and help. A caring personality willing to cooperate and participate in various social activities in the community [23]. Caring for others is defined as a form of caring in the surrounding environment by providing assistance if someone needs or being empathetic to people who have serious problems.…”
Section: Care Of Othersmentioning
confidence: 99%
“…In a literary work, some values, such as social, cultural, character, moral, and ethical or habitual values, reflect life. The short stories in the textbook contain 12 character education values, including religion, honesty, tolerance, discipline, hard work, creativity, independence, democracy, curiosity, national spirit, and friendship [7].…”
Section: Introductionmentioning
confidence: 99%